SFRS7-mediated splicing of tau exon 10 is directly regulated by STOX1A in glial cells. - Daan van Abel (Public Library of Science (PLoS), 2011)
Background In this study, we performed a genome-wide search for effector genes bound by STOX1A, a winged helix transcription factor recently demonstrated to be involved in late onset Alzheimer's disease and affecting the amyloid processing pathway. Methodology/principal findings Our results show that out of 218 genes bound by STOX1A as identified by chromatin-immunoprecipitation followed by sequencing (ChIP-Seq), the serine/arginine-rich splicing factor 7 (SFRS7) was found to be induced, both at the mRNA and protein levels, by STOX1A after stable transfection in glial cells. The increase in SFRS7 was followed by an increase in the 4R/3R ratios of the microtubule-associated protein tau (MAPT) by differential exon 10 splicing. Secondly, STOX1A also induced expression of total tau both at the mRNA and protein levels. Upregulation of total tau expression (SFRS7-independent) and tau exon 10 splicing (SFRS7-dependent), as shown in this study to be both affected by STOX1A, is known to have implications in neurodegeneration. Conclusions Our data further supports the functional importance and central role of STOX1A in neurodegeneration.